Kedudukan Hukum dan Tanggung Jawab Perdata Kecerdasan Buatan (AI) Generatif dalam Perjanjian Elektronik: Tantangan Asas Pacta Sunt Servanda di Era Digital - Anugrah Ryandra Fahlevi; Muhammad Saddam Safa (ILIN Institute, 2026)
The rapid development of Generative Artificial Intelligence (AI) has significantly transformed electronic transactions and digital contracting practices. AI systems are increasingly involved in drafting, negotiating, and executing electronic agreements, raising legal questions regarding their legal standing and civil liability. This study aims to analyze the legal position of Generative AI in electronic contracts and examine the challenges posed to the principle of pacta sunt servanda in the digital era. The research employs normative legal methods using statutory, conceptual, and comparative approaches. The findings indicate that Generative AI does not possess legal personality and therefore cannot independently bear legal rights and obligations. Civil liability arising from AI-generated actions remains attached to developers, service providers, business actors, or users depending on the circumstances. Furthermore, the increasing autonomy of AI systems creates challenges in determining consent, accountability, and contractual validity. The study concludes that Indonesian law requires adaptive legal frameworks to ensure legal certainty and protection for parties involved in AI-assisted electronic contracts.